PENGGUNAAN METODE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PAI DI SDN 06 KEDONDONG DESA TEMPEL REJO KAB. PESAWARAN TAHUN PELAJARAN - Eka Pangesti; Ahmad Fathoni; Nurul Aslamiah (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
The Jigsaw method is a pretty good method. It is hoped that after implementing this method it can have a positive impact on learning outcomes. The concept of innovative learning using the jigsaw method seems to encourage teachers and students to apply practice actively and creatively so that it is hoped that improved learning outcomes can be achieved. The background of the problem based on the low student learning outcomes in PAI subjects is an indication that the lessons carried out so far have not achieved completeness due to several factors, namely learning that is still used using the lecture method, making question and answer questions and assignments. So the problem formulation is whether the use of the Jigsaw Learning Model can improve learning outcomes at PAI SDN 06 Kedondong, Tempel Rejo Village, Kab. Pesawaran Academic Year 2023/2024. This research is Classroom Action Research (PTK) which consists of two cycles. By using observation methods, interview methods, methods documentation and testing methods used to support this research. By implementing this learning strategy, students wil be motivated to study more actively and want to read the material provided by the teacher, because Learning will be more varied and fun so that it can improve learning outcomes.Based on the research results, it can be concluded that the learning method. The jigsaw that has been applied to PAI subjects can improve the learning outcomes of students at SDN 06 Kedondong. This can be seen from the improvement in cycle I to cycle II in the learning process using the jigsaw learning model. During the pre-cycle, there were 15 students who had not yet achieved completeness and 7 students who had achieved completeness. In the first cycle of the first meeting, there were 9 students who had achieved completeness and 12 students who had not achieved completeness. In the first cycle of the second meeting, there were 11 students who had achieved completeness and 11 students who had not achieved completeness. In cycle II of the first meeting, 14 students completed and 8 students did not complete. In the second cycle, there were 18 students who had achieved completeness and 4 students who had not achieved completeness.